MAPEAMENTO DE FLUXO DE VALOR NA ELABORAÇÃO DE PROJETO HIDRÁULICO COM UTILIZAÇÃO DE MÉTODO TRADICIONAL E O REVIT - Leite, Lucas; Veras, Rodrigo; Jereissati, Geórgia; Morais, Tiago (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
The financial crisis in recent years has been affecting brazilian construction sector. In spite of this, construction companies are constantly innovating to keep their clients with new methods and technologies in order to be able to reduce significantly the waste and costs. The use of Building Information Modeling (BIM),- a digital representation of the physical and functional characteristics of a building, serving as a source of shared information and data about it - appears as one of the resources to assist the development and understanding their projects and execution. The Lean has several methods, among them, the Value Stream Mapping (VSM), which main objective is to show the wastes contained in the production system and propose improvements. This paper aims to present the VSM through the creating a hydraulic project of a residential building and compare the results obtained with the use of Autocad and Revit softwares. Associated with the use of BIM, Lean practices were also introduced, aiming to improve productivity, reduce losses, and guarantee better quality to the system. The result found was a reduction of approximately 54% of the Permanence Time, generated by the application of the VSM of the future state using the BIM.